Effect of Casein Phosphopeptide Amorphous Calcium Phosphate and Xylitol Chewing Gums, and Probiotic Yogurt on Periodontal Parameters: A Randomized Clinical Trial - Vajihe Barati; Maryam Mehrabkhani; Iman Parisay; Niayesh Mastoori (Tehran University of Medical Sciences, 2021)
Objectives: This study aimed to assess the effect of casein phosphopeptide amorphous calcium phosphate (CPP-ACP) and xylitol chewing gums, and probiotic yogurt, as chemical plaque control strategies, on periodontal parameters. Materials and Methods: This randomized clinical trial evaluated 120 eligible dental students that were randomly divided into four groups (n=30) for use of (I) CPP-ACP chewing gum, (II) xylitol chewing gum, (III) probiotic yogurt, and (IV) chlorhexidine (CHX) mouthwash. The oral hygiene index-simplified (OHI-S), Silness and Loe gingival index (GI), and Silness and Loe modified plaque index (PI) were measured before and on days 15 and 30 after using the products. Paired t-test or its non-parametric equivalent was used to analyze the parameters after the intervention compared with baseline. The study groups were compared using one-way ANOVA or its non-parametric equivalent. Results: The OHI-S did not change over time, and most participants had a good OHI-S. The CHX group had the most favorable, and the probiotic yogurt group had the least favorable GI. Pairwise comparisons of the groups did not reveal a significant difference in GI between the CPP-ACP gum and CHX groups (P>0.05). CHX caused the greatest improvement in PI, with significant differences with other groups. Conclusion: CHX was the most effective for improvement of periodontal parameters followed by CPP-ACP, which showed better results compared with other groups.